Challenges and Technology Trends in Implementing a Human Resource Management System: A Systematic Literature Review - Rahma Destriani; Raihansyah Yoga Adhitama; Dana Indra Sensuse; Deden Sumirat Hidayat; Erisva Hakiki Purwaningsih (Journal of Information Systems Engineering and Business Intelligence)
Background: Human Resource Management System (HRMS) is an important aspect of managing organizations. However, the successful integration of the system into respective roles is often associated with diverse technological challenges and trends. Some major obstacles identified in recent research include reluctance to change, lack of training, fragmented Human Resource (HR) data, rigid processes, and continuous changes in organizational needs. Exciting technology trends offer promise for next-generation HRMS solutions, including artificial intelligence (AI), machine learning, predictive analytics, and mobile accessibility. This shows the need for a systematic literature review to comprehensively map the challenges and technology trends shaping the implementation of HRMS.